Zebrafish Tyrosine Hydroxylase 2 Gene Encodes Tryptophan Hydroxylase - Ren, Guiqi (American Society for Biochemistry and Molecular Biology, 2013)
The primary pathological hallmark of Parkinson disease (PD) is the profound loss of dopaminergic neurons in the substantia nigra pars compacta. To facilitate the understanding of the underling mechanism of PD, several zebrafish PD models have been generated to recapitulate the characteristics of dopaminergic (DA) neuron loss. In zebrafish studies, tyrosine hydroxylase 1 (th1) has been frequently used as a molecular marker of DA neurons. However, th1 also labels norepinephrine and epinephrine neurons. Recently, a homologue of th1, named tyrosine hydroxylase 2 (th2), was identified based on the sequence homology and subsequently used as a novel marker of DA neurons. In this study, we present evidence that th2 co-localizes with serotonin in the ventral diencephalon and caudal hypothalamus in zebrafish embryos. In addition, knockdown of th2 reduces the level of serotonin in the corresponding th2-positive neurons. This phenotype can be rescued by both zebrafish th2 and mouse tryptophan hydroxylase 1 (Tph1) mRNA as well as by 5-hydroxytryptophan, the product of tryptophan hydroxylase. Moreover, the purified Th2 protein has tryptophan hydroxylase activity comparable with that of the mouse TPH1 protein in vitro. Based on these in vivo and in vitro results, we conclude that th2 is a gene encoding for tryptophan hydroxylase and should be used as a marker gene of serotonergic neurons.